(untitled) (Ibrahim Medical College Journal, 2009)
The prevalence of congenital abnormalities of coronary artery is about 2% of general population. Of these abnormalities 5% were related to coronary artery fistulae (CAF). We report a case of 66 year old diabetic woman who presented with retrosternal chest pain. Her chest pain was associated with exercise and progressively deteriorated over the last 6 months. Electrocardiography showed right bundle branch block and Echo Color Doppler revealed hypo kinetic lateral wall. Coronary angiogram detected nothing abnormal except an aberrant tortuous branch of left circumflex. CT scan revealed a calcified sac medial to the descended thoracic aorta. A contrast enhancement was also done. All these imaging impressions were suggestive of coronary-to-pulmonary fistula. Key Words: Coronary Artery; abnormalities Ibrahim Med. Coll. J. 2007; 1(1): 32-33 doi: 10.3329/imcj.v1i1.2892